Analytic Study of Sportive Injuries of Students of Sport Faculty Tishreen University (Reasons and Prevention Methods) (Latakia University Journal -Medical Sciences Series, 2020)
The research is considered an analytic study which aims to know different kinds of sportive injuries which some students of sport faculty of Tishreen University have, and the reasons behind them and the places they occur in.The study covered the four years students and aimed to reach preventive foundations the study courses may contain.The study also contains recommendations associated with the infrastructure in the place of training and ways of restraining lessons.The study have involved (116) scorbutic out of (980) students which is the total society of the study.The results were as follows the lower extremities are the most affected especially the knee and ankle joint, the biggest percentage was in the first years and second year, the most important reasons are overheating shortage and the lack of preparation, the injures biggest rate is in athletics then comes the gymnasium.